NUTRITION IN VIRAL HEPATITIS (Multidisciplinary Journal of Science and Technology, 2025)
Acute viral hepatitis (AVH) is an inflammation of liver tissue, primarily caused by viral infections. The main types include hepatitis A, B, C, D, and E viruses. The disease leads to liver cell damage and impaired function, making proper nutrition crucial. The liver plays a vital role in metabolism, detoxification, and the synthesis of proteins, carbohydrates, and fats. During AVH, these processes may be disrupted, so adhering to a special diet helps protect the liver from excessive strain.